Systemic Lupus Erythematosus in Primary Care: An Update and Practical Messages for the General Practitioner - Gergianaki, Irini; Bertsias, George (Frontiers in Medicine, 2018)
Systemic Lupus Erythematosus (SLE) is a complex chronic autoimmune disease that manifests a wide range of organ involvement. Traditionally, the diagnosis and management of SLE is provided at secondary and tertiary centers to ensure prompt initiation of treatment, adequate control of flares and prevention of irreversible organ damage. Notwithstanding, the role of primary care in SLE is also emerging as there are still significant unmet needs such as the diagnostic delay at the community level and the high burden of therapy- and disease-related comorbidities. In the present review, we summarize practical messages for primary care physicians and general practitioners (GPs) concerning early diagnosis and proper referral of patients with SLE. In addition, we discuss the main comorbidities complicating the disease course and the recommended preventive measures, and we also provide an update on the role and current educational needs of GPs regarding the disease.